Conventional and genetic evidence on the association between adiposity and CKD - Zhu, P; Herrington, WG; Haynes, R; Emberson, J; Landray, MJ; Sudlow, CLM; Woodward, M; Baigent, C; Lewington, S; Staplin, N (American Society of Nephrology, 2020)
Background The size of any causal contribution of central and general adiposity to CKD risk and the underlying mechanism of mediation are unknown.